2009
DOI: 10.1105/tpc.108.064329
|View full text |Cite
|
Sign up to set email alerts
|

Tissue- and Expression Level–Specific Chromatin Looping at Maizeb1Epialleles

Abstract: This work examines the involvement of chromatin looping in the transcriptional regulation of two epialleles of the maize (Zea mays) b1 gene, B-I and B'. These two epialleles are tissue-specifically regulated and are involved in paramutation. B-I and B' are expressed at high and low levels, respectively. A hepta-repeat ;100 kb upstream of the transcription start site (TSS) is required for both paramutation and high b1 expression. Using chromosome conformation capture, we show that the heptarepeat physically int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
137
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 128 publications
(144 citation statements)
references
References 45 publications
4
137
0
Order By: Relevance
“…Moreover, whereas B-I reverts spontaneously to B 0 at high frequency (1-10%) and can thus be considered a metastable epiallele, B 0 is highly stable and only becomes more active in RNAi mutant backgrounds (Dorweiler et al, 2000;Alleman et al, 2006;Woodhouse et al, 2006). These findings suggest that the tandem repeats of B-I and B 0 are, respectively, just below and well above the threshold required for RNAi-dependent chromatin targeting, presumably as a consequence of differences in chromatin states (Stam et al, 2002;Louwers et al, 2009). Although the available evidence seems to indicate otherwise (Arteaga-Vazquez and Chandler, 2010), it is also reasonable to assume that the tandem repeats of B 0 and B-I produce distinct amount of siRNAs, at least during the reproductive phase, when the RNAi-dependent chromatin targeting pathway could be most active, as in Arabidopsis (Figure 2).…”
Section: Variation In Rddm Strength and Paramutationmentioning
confidence: 79%
See 1 more Smart Citation
“…Moreover, whereas B-I reverts spontaneously to B 0 at high frequency (1-10%) and can thus be considered a metastable epiallele, B 0 is highly stable and only becomes more active in RNAi mutant backgrounds (Dorweiler et al, 2000;Alleman et al, 2006;Woodhouse et al, 2006). These findings suggest that the tandem repeats of B-I and B 0 are, respectively, just below and well above the threshold required for RNAi-dependent chromatin targeting, presumably as a consequence of differences in chromatin states (Stam et al, 2002;Louwers et al, 2009). Although the available evidence seems to indicate otherwise (Arteaga-Vazquez and Chandler, 2010), it is also reasonable to assume that the tandem repeats of B 0 and B-I produce distinct amount of siRNAs, at least during the reproductive phase, when the RNAi-dependent chromatin targeting pathway could be most active, as in Arabidopsis (Figure 2).…”
Section: Variation In Rddm Strength and Paramutationmentioning
confidence: 79%
“…This allele exists in two epiallelic forms, B-I and B 0 , which are strongly and weakly active, respectively. Difference in expression is associated with differential DNA methylation and chromatin accessibility of a set of seven tandem repeats that act as enhancers and that are located 100 kb upstream of the b1 transcription start site (Stam et al, 2002;Louwers et al, 2009). These seven tandem repeats are responsible for mediating in F1 heterozygotes the transfer of the expression state of paramutagenic B 0 to paramutable B-I with 100% penetrance and in an RNAi-dependent manner.…”
Section: Variation In Rddm Strength and Paramutationmentioning
confidence: 99%
“…The existing protocols for the last two methods cannot simply be transferred to plant tissues due to the special properties and unique chemical composition of plants. In this paper we provide a maize-specific 3C protocol that we recently developed and successfully applied 14 . Moreover, we present a general strategy to systematically optimize the protocol for other plants.…”
Section: Methods To Investigate Chromatin Interactionsmentioning
confidence: 99%
“…The tandem repeats mediate enhancer activity that functions in cis to increase transcription from the b1 gene when in the B-I state (20), potentially through a long-distance looping mechanism because the tandem repeats interact with the transcription start site of the b1 gene differentially in B-I vs. B′ (23). The molecular nature of the genes required for paramutation strongly suggests that an RNA-dependent mechanism is critical for paramutation.…”
mentioning
confidence: 99%
“…This sequence is unique to this location within the maize genome, and both B-I and B′ carry seven tandem repeats, whereas alleles that do not undergo paramutation have a single copy of the repeat unit (20,21). B-I and B′ are epialleles; that is, they have identical DNA sequences but show distinct patterns of DNA methylation and chromatin structure within the tandem repeats (20,(22)(23)(24). Generation of an allelic series with different numbers of repeats demonstrated that multiple repeats are required for paramutation (20).…”
mentioning
confidence: 99%